2009
DOI: 10.1515/epoly.2009.9.1.886
|View full text |Cite
|
Sign up to set email alerts
|

pH-Driven synthesis of collagen-silica nanohybrids

Abstract: Immobilization of the protein collagen Type I into transparent porous silica matrices produced by the sol-gel process was achieved by using a high concentration of precursor and a low pH. Surface silanol groups interact chemically with the amide and carboxylic groups of the collagen Type I to produce a novel nanohybrid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…39 This could be due to the interactions between the amino groups of SF and the -OH group of hydrolyzed TEOS. 40 In addition, the presence of characteristic peaks observed in the fingerprint region of SF/ BG samples further confirm the interactions of BG with SF. More detailed FTIR spectra are shown in Fig.…”
Section: Structural and Compositional Characterizationmentioning
confidence: 56%
“…39 This could be due to the interactions between the amino groups of SF and the -OH group of hydrolyzed TEOS. 40 In addition, the presence of characteristic peaks observed in the fingerprint region of SF/ BG samples further confirm the interactions of BG with SF. More detailed FTIR spectra are shown in Fig.…”
Section: Structural and Compositional Characterizationmentioning
confidence: 56%
“…FTIR analysis of collagen-silica nanohybrids obtained by mixing solventdenatured collagen with hydrolyzed TEOS was also reported. 136 It was suggested that hydrogen bonds exist between the silanol groups of the silica and carboxyl, hydroxyl and amino groups of the collagen.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…Collagen-templated silica has been synthesized under various conditions: with different kinds of precursors (TEOS, tetramethoxysilane and Na 2 SiO 3 ), with or without a catalyst for the hydrolysis of the precursor and varying states of collagen (solution or gelled). [20][21][22] However, the reported methods are time consuming and have shown limited structural reproducibility and dispersion of the fibrous silica.…”
mentioning
confidence: 99%